Beyond Compliance: Interpretive Content Analysis of Shariah Governance Disclosures in Indonesian Islamic Banks - Prasojo; Romzie Rosman; Dwi Marlina Wijayanti; Rosyid Nur Anggara Putra; Lailatis Syarifah (ccounting Department, Universitas Syiah Kuala, Indonesia, 2026)
This study examines the quality of Shariah Governance (SG) disclosures among Indonesian Islamic banks during 2020-2024 using 65 bank-year observations from 13 Islamic banks. An explanatory-sequential mixed-methods approach combines a structured disclosure checklist, interpretive rubric, and cluster analysis to assess reporting practices. Two disclosure tendencies emerge: strategic disclosure and transitional compliance. Banks with stronger SSB characteristics tend to present more developed disclosure narratives, while formal governance structures alone show weaker associations. The findings suggest that disclosure quality reflects institutional capability and supervisory practices beyond structural arrangements.